Effect of lidocaine on the minimum alveolar concentration of sevoflurane in dogs - Matsubara, Lidia M.; Oliva, Valeria Nobre Leal de Souza [UNESP]; Gabas, Daniela Tozadore [UNESP]; Oliveira, Guillermo C. V.; Cassetari, Maria L. [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
ObjectiveTo investigate the effects of a low-dose constant rate infusion (LCRI; 50 mu g kg(-1) minute(-1)) and high-dose CRI (HCRI; 200 mu g kg(-1) minute(-1)) lidocaine on arterial blood pressure and on the minimum alveolar concentration (MAC) of sevoflurane (Sevo), in dogs.Study designProspective, randomized experimental design.AnimalsEight healthy adult spayed female dogs, weighing 16.0 +/- 2.1 kg.MethodsEach dog was anesthetized with sevoflurane in oxygen and mechanically ventilated, on three separate occasions 7 days apart. Following a 40-minute equilibration period, a 0.1-mL kg(-1) saline loading dose or lidocaine (2 mg kg(-1) intravenously) was administered over 3 minutes, followed by saline CRI or lidocaine LCRI or HCRI. The sevoflurane MAC was determined using a tail clamp. Heart rate (HR), blood pressure and plasma concentration of lidocaine were measured. All values are expressed as mean +/- SD.ResultsThe MAC of Sevo was 2.30 +/- 0.19%. The LCRI reduced MAC by 15% to 1.95 +/- 0.23% and HCRI by 37% to 1.45 +/- 0.21%. Diastolic and mean pressure increased with HCRI. Lidocaine plasma concentration was 0.84 +/- 0.18 for LCRI and 1.89 +/- 0.37 mu g mL(-1) for HCRI. Seventy-five percent of HCRI dogs vomited during recovery.Conclusion and clinical relevanceLidocaine infusions dose dependently decreased the MAC of Sevo, did not induce clinically significant changes in HR or arterial blood pressure, but vomiting was common during recovery in HCRI.
Keywords: blood pressure; constant rate infusion; dog; lidocaine; minimum alveolar concentration; sevoflurane